A novel widespread cryptic species and phylogeographic patterns within several giant clam species (Cardiidae: Tridacna) from the Indo-Pacific Ocean. - Thomas Huelsken; Jude Keyse; Libby Liggins; Shane Penny; Eric A Treml; Cynthia Riginos (PLoS ONE, 2013)
Giant clams (genus Tridacna) are iconic coral reef animals of the Indian and Pacific Oceans, easily recognizable by their massive shells and vibrantly colored mantle tissue. Most Tridacna species are listed by CITES and the IUCN Redlist, as their populations have been extensively harvested and depleted in many regions. Here, we survey Tridacna crocea and Tridacna maxima from the eastern Indian and western Pacific Oceans for mitochondrial (COI and 16S) and nuclear (ITS) sequence variation and consolidate these data with previous published results using phylogenetic analyses. We find deep intraspecific differentiation within both T. crocea and T. maxima. In T. crocea we describe a previously undocumented phylogeographic division to the east of Cenderawasih Bay (northwest New Guinea), whereas for T. maxima the previously described, distinctive lineage of Cenderawasih Bay can be seen to also typify western Pacific populations. Furthermore, we find an undescribed, monophyletic group that is evolutionarily distinct from named Tridacna species at both mitochondrial and nuclear loci. This cryptic taxon is geographically widespread with a range extent that minimally includes much of the central Indo-Pacific region. Our results reinforce the emerging paradigm that cryptic species are common among marine invertebrates, even for conspicuous and culturally significant taxa. Additionally, our results add to identified locations of genetic differentiation across the central Indo-Pacific and highlight how phylogeographic patterns may differ even between closely related and co-distributed species.